2018
DOI: 10.1111/nmo.13326
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐induced colonic slow transit mediated by the up‐regulation of PDGFRα+ cells/SK3 in streptozotocin‐induced diabetic mice

Abstract: These results suggest that the purinergic neurotransmitters/P2Y1/SK3 signaling pathway is up-regulated in the diabetic colons, thereby mediating diabetes-induced colonic slow transit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 39 publications
(95 reference statements)
0
27
0
Order By: Relevance
“…PDGFRα + cells express SK3 protein. Inhibitory neurotransmitters, mainly purines bind to G-protein coupled P2Y1 receptors in PDGFRα + cells, 4,9,36 increase intracellular Ca 2+ , activate SK3 channels, and induce hyperpolarization. 37,38 In the present study, western blot displayed that the Pdgfra and SK3 proteins were significantly upregulated in PCO colon compared with those of control mice.…”
Section: Discussionmentioning
confidence: 99%
“…PDGFRα + cells express SK3 protein. Inhibitory neurotransmitters, mainly purines bind to G-protein coupled P2Y1 receptors in PDGFRα + cells, 4,9,36 increase intracellular Ca 2+ , activate SK3 channels, and induce hyperpolarization. 37,38 In the present study, western blot displayed that the Pdgfra and SK3 proteins were significantly upregulated in PCO colon compared with those of control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although synaptic-like contacts between nerve varicosities and TCs were not observed under the TEM, it has been demonstrated that TCs express purine receptors P2Y1 and apamin-sensitive SK3 channels and respond to agonists and antagonists to these receptors [ 18 , 19 , 41 , 42 , 43 ]. Furthermore, the TCs/PDGFRα-positive cells selectively expressed the SK3 channel among all the ICs present in the gut interstitium [ 44 ] and significant changes in the functionality of these receptors have been associated with GI diseases [ 45 , 46 , 47 ]. TCs also contain soluble guanylyl cyclase and it has been speculated that they could function as neural transducers responding to ATP and nitric oxide [ 19 , 40 ].…”
Section: Telocytesmentioning
confidence: 99%
“…EFS induced biphasic IJPs in control colonic muscles, consisting of a fast hyperpolarization (fIJP), following with a more stable hyperpolarization reaction (sIJP) that continued till the stimulus ended. 26,27 In the following experiments, the amplitudes of sIJPs were recorded in control and DSS-colitis mice. In the proximal colon of the control mice, EFS (50 V; 3, 6, and 9 Hz; 5 seconds) induced a continuous hyperpolarization after the fIJPs, and the average amplitudes of sIJPs were 3.3 ± 0.3, 7.6 ± 0.4, and 13.7 ± 0.4 mV (n = 7; Fig.…”
Section: Changes In Electrical Field Stimulation-induced Slow Inhibitmentioning
confidence: 99%